Benziodoxole-Derived Organosulfonates: The Strongest Hypervalent Iodine Electrophiles and Oxidants; Synlett; Vol. 31, № 4 - Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Postnikov P. S. Pavel Sergeevich; Yoshimura A. Akira; Zhdankin V. V. Viktor (2020, 2020)
Title screen